First-year hemp farmers’ motives and resources to cultivate hemp - Blake Colclasure; Jason Caldwell; Tyler Granberry; Christine Rost; Bailey Gasseling (Journal of Agriculture, Food Systems, and Community Development)
Recent legislative changes have opened new avenues of hemp production for farmers seeking to diversify their operations. With the availability of these opportunities comes the need to better understand the decision making processes of new hemp growers. The purpose of this study was to explore what motivated first-year hemp farmers to grow hemp and to better understand the resources they utilized for decision-making. Fifteen farmers engaged in one-on-one interviews, which were analyzed using qualitative research methods. Three distinct themes emerged that undergirded farmer motivations to grow hemp: personal characteristics, identified advantages of hemp as a crop, and trialability and compatibility. Additionally, four themes were central to the resources new hemp farmers sought out: grower networks, digital media, government-based resources, and print media. The findings of this study align with components of Rogers’ Diffusion of Innovation Theory and recent research related to hemp and hemp-based products. Based on these findings, we recommend developing and expanding educational resources for those interested in entering hemp production to aid in their decision-making process and assist them as they navigate their entry into hemp cultivation.